Effectiveness of virtual mindfulness-based interventions on perceived anxiety and depression of physicians during the COVID-19 pandemic: A pre-post experimental study - Al Ozairi, Abdullah; Alsaeed, Dalal; Al-Ozairi, Ebaa; Irshad, Mohammad; Crane, Rebecca S.; Almoula, Aroub (Frontiers in Psychiatry, 2023)
Background The outbreak of coronavirus disease 2019 (COVID-19) created unprecedented stress on physicians. Mindfulness is a type of meditation that focuses on being fully present, aware of senses, and emotions in the present moment without analyzing or judging them, and it may help reduce psychological distress in physicians. This study aimed to examine the effectiveness of virtual mindfulness-based intervention (MBI) on physicians’ perceived anxiety and depression and different facets of mindfulness. Methods During the COVID-19 pandemic, an online survey was administered to physicians to assess depression, anxiety, and awareness using the 9-item Patient Health Questionnaire (PHQ-9), 7-item General Anxiety Disorder (GAD-7), and Five-Facets Mindfulness Questionnaire (FFMQ), respectively. Physicians that received the virtual MBI sessions also completed post-questionnaires at a 3-week follow-up time point. Results A total of 125 physicians responded to the online survey, with 56 completing the MBI. The prevalence of moderate to severe anxiety and depression was 45.0 and 46.7%, respectively. Mindfulness scores were negatively associated with depression (r = −0.38, P < 0.001) and anxiety (r = −0.36, p < 0.001). Mindfulness scores for the 56 physicians who received virtual MBI sessions were significantly improved (mean difference ± SD, 17.7 ± 16.1, p = 0.001). Significant reductions were also evidenced in anxiety (4.4 ± 4.2) and depression (4.5 ± 5.1) scores (p’s < 0.001). There was also an improvement in mindfulness facets of observing (5.1 ± 4.7), describing (2.3 ± 4.3), acting with awareness (2.7 ± 5.3), non-judging of inner experience (3.6 ± 6.1), and non-reactivity to inner experience (3.9 ± 4.0) (p’s < 0.001). A facet of mindfulness, acting with awareness was most efficiently associated with improved anxiety (B = −0.3, p = 0.02) and depression (B = −0.4, p = 0.01). Conclusion This study has demonstrated that virtual MBI improved physicians’ psychological wellbeing and mindfulness during the crisis. Regular mindfulness practice may help physicians to tolerate and handle unpleasant circumstances, such as future epidemics or pandemics.